William Shakespeare y otras referencias literarias en The Diviners, de Margaret Laurence. - López Esteve, Juan Antonio (Estudios Ingleses de la Universidad Complutense, 2001)
This paper has picked up and analysed the explicit and implicit intertextual elements from Shakespeare in The Diviners, by Margaret Laurence, and found that they are significant clues to let us draw out the latter's opinion about the former his belonging to tradition, his being still alive for young people, and his importance along her own literary life, as well as The Tempest's clear and subtle links to her novel. The paper has also looked into the bio-bibliography of Margaret Laurence to validate, or not, its own conclusions. 1.